The Homeroom Teacher's Approach as a Guidance Counselor in Building Student Character in an Elementary School - Rahmawati, Rahmawati; Achmad, Listian Indriyani; Setyowati, Rini; Nenda, Nenda; Ali, Saiful Mukti; Nugroho, Djoko (Proceeding International Pelita Bangsa, 2023)
The purpose of this research is to find out the role of the homeroom teacher as a guidance counselor in building students' character in elementary schools. This type of research is qualitative research. Interviews were conducted homeroom teachers. This interview was on their approach in building student discipline character. The interview method was one-on-one. Then the data is presented in the form of excerpts from the interview results. The results of the research show that building the students’ character is done through continuous guidance: directing students towards good deeds, convincing students of the importance of discipline, giving reprimands, and punishing those who violate school rules.